Mental Simulation of Facial Expressions: Mu Suppression to the Viewing of Dynamic Neutral Face Videos - Karakale, Ozge; Moore, Matthew R.; Kirk, Ian J. (Frontiers in Human Neuroscience, 2019)
The mirror neuron network (MNN) has been proposed as a neural substrate of action understanding. Electroencephalography (EEG) mu suppression has commonly been studied as an index of MNN activity during execution and observation of hand and finger movements. However, in order to establish its role in higher order processes, such as recognising and sharing emotions, more research using social emotional stimuli is needed. The current study aims to contribute to our understanding of the sensitivity of mu suppression to facial expressions. Modulation of the mu and occipital alpha (8 - 13 Hz) rhythms was calculated in 22 participants while they observed dynamic video stimuli, including emotional (happy and sad) and neutral (mouth opening) facial expressions, and non-biological stimulus (kaleidoscope pattern). Across the four types of stimuli, only the neutral face was associated with a significantly stronger mu suppression than the non-biological stimulus. Occipital alpha suppression was significantly greater in the non-biological stimulus than all the face conditions. Source estimation (sLORETA) analysis comparing the neural sources of mu/alpha modulation between neutral face and non-biological stimulus showed more suppression in the central regions, including the supplementary motor and somatosensory areas, than the more posterior regions. EEG and source estimation results may indicate that reduced availability of emotional information in the neutral face condition requires more sensorimotor engagement in deciphering emotion-related information than the full-blown happy or sad expressions that are more readily recognised.